1996
DOI: 10.1016/0020-7462(96)00025-x
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a class of non-normal random processes

Abstract: Abstract-This study addresses the simulation of a class of non-normal processes based on measured samples and sample characteristics of the system input and output. The class of nonnormal processes considered here concerns environmental loads, such as wind and wave loads, and associated structural responses. First, static transformation techniques are used to perform simulations of the underlying Gaussian time or autocorrelationsample. An optimization procedure is employed to overcome errors associated with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(31 citation statements)
references
References 17 publications
(9 reference statements)
0
31
0
Order By: Relevance
“…Those which seek to produce sample functions matching the prescribed power spectral density function (SDF) and lower-order statistics (mean, variance, skewness and kurtosis) of a target stochastic field e.g. [85,86] and those seeking to generate sample functions compatible to complete probabilistic information. The first type of methods are suitable for the simulation of wind and wave loads, for which generation of non-Gaussian sample functions according to prescribed lower-order moments will provide accurate results for the stochastic response [86].…”
Section: Simulation Methods For Non-gaussian Stochastic Processes Andmentioning
confidence: 99%
“…Those which seek to produce sample functions matching the prescribed power spectral density function (SDF) and lower-order statistics (mean, variance, skewness and kurtosis) of a target stochastic field e.g. [85,86] and those seeking to generate sample functions compatible to complete probabilistic information. The first type of methods are suitable for the simulation of wind and wave loads, for which generation of non-Gaussian sample functions according to prescribed lower-order moments will provide accurate results for the stochastic response [86].…”
Section: Simulation Methods For Non-gaussian Stochastic Processes Andmentioning
confidence: 99%
“…Early work based on correlation distortion has been based on an inverse mapping of the desired probability density function, a summary of which may be found in Gurley et al (1996). In Gurley and , a simulation approach, which is significantly more robust than the correlation distortion schemes, was presented.…”
Section: Static Transformation Schemesmentioning
confidence: 99%
“…Gurley et al (1996) utilized Neural networks to simulate non-Gaussian pressure time histories and demonstrated that due to the static nature of the approach, the simulated time history did not reflect the memory in the process as evidenced by the lack of good comparison with the target bi-spectra and the bispectra of the simulated record using Volterra kernel of Neural networks (Gurley et al 1996 and1997).…”
Section: Other Approachesmentioning
confidence: 99%
“…Let X denote the collection of stochastic processes defined by the finite dimensional distributions and densities in Eqs. (8) and (9). A member X of X is called a mixture of translation processes.…”
Section: The Class Of Mixtures Of Translation Processesmentioning
confidence: 99%
“…These feature of the mixtures of translation processes can be very useful in some applications. For example, if the available information on a time series consists of the marginal distribution and the first and second order correlation functions [9], translation processes can be inadequate. The samples in Fig.…”
Section: Monte Carlo Simulation Algorithmmentioning
confidence: 99%